2021
DOI: 10.1186/s12884-021-03999-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient perceptions of the benefits and barriers of virtual postnatal care: a qualitative study

Abstract: Objective The objective of this study is to understand the perceptions of new mothers using virtual care via video conferencing to gain insight into the benefits and barriers of virtual care for obstetric patients. Methods Semi-structured interviews were conducted with 15 patients attending the Kingston Health Sciences Centre. The interviews were 20–25 min in length and recorded through an audio recorder. Thematic analysis was conducted in order to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 30 publications
(29 reference statements)
0
16
0
Order By: Relevance
“…While remote healthcare appointments may have increased access to healthcare among some groups during the pandemic, offering appointments remotely in the future is not likely to be a preference reported by all, particularly for those with serious health concerns [ 47 ]. Qualitative research interviews conducted in Canada suggest that women may prefer virtual postnatal care because it helps to regulate their family routine, reduce stress and save on expenses associated with travel to consultations [ 48 ]. However, for participants in our study experiencing a first pregnancy, pregnancy complications or a pre-existing health condition, compulsory remote care was a source of great concern, leading to feelings of uncertainty and increased stress.…”
Section: Discussionmentioning
confidence: 99%
“…While remote healthcare appointments may have increased access to healthcare among some groups during the pandemic, offering appointments remotely in the future is not likely to be a preference reported by all, particularly for those with serious health concerns [ 47 ]. Qualitative research interviews conducted in Canada suggest that women may prefer virtual postnatal care because it helps to regulate their family routine, reduce stress and save on expenses associated with travel to consultations [ 48 ]. However, for participants in our study experiencing a first pregnancy, pregnancy complications or a pre-existing health condition, compulsory remote care was a source of great concern, leading to feelings of uncertainty and increased stress.…”
Section: Discussionmentioning
confidence: 99%
“…21 It is clear that virtual care is well tolerated by patients and, in some cases, preferred. 22 Clinicians have found it effective and perhaps superior to a traditional care model. 23 How this is reimbursed will impact the development of these services.…”
Section: Implementation Modelsmentioning
confidence: 99%
“…One of the most commonly reported covid-related changes to all forms of service provision in maternity care has been an increase in the use of remote/virtual consultations using telephone or video 4 7 10–18. For example, one recent survey of all 194 obstetric units in England (42% response rate) found that 89% reported using digitally delivered consultation methods in antenatal care and 56.8% for postnatal care 7.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, existing research on DC-CON in maternity care shows that it can be safe and acceptable in controlled conditions 27–29 35 37–41. Research also shows that the experiences of staff and women with DC-CON vary quite significantly 7 12 34 39 42–50. A gap remains, therefore, in understanding the conditions required for safe and acceptable DC-CON implementation and in understanding the factors that underpin variation in experience.…”
Section: Introductionmentioning
confidence: 99%